2007
DOI: 10.1371/journal.pone.0000911
|View full text |Cite
|
Sign up to set email alerts
|

Direct Selection on Genetic Robustness Revealed in the Yeast Transcriptome

Abstract: BackgroundEvolutionary theory predicts that organisms should evolve the ability to produce high fitness phenotypes in the face of environmental disturbances (environmental robustness) or genetic mutations (genetic robustness). While several studies have uncovered mechanisms that lead to both environmental and genetic robustness, we have yet to understand why some components of the genome are more robust than others. According to evolutionary theory, environmental and genetic robustness will have different resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…Similar result were previously reported for Drosophila melanogaster [18] and Saccharomyces cerevisiae [19]. The positive association of V E with V G is consistent with the idea that genetic and environmental canalization may have common underlying mechanisms [20], [21], [22]. The positive association between V M and V E has an important implication, because theory predicts that genetic robustness is much more likely to evolve via correlated responses to selection for environmental robustness than via direct selection [11], [20].…”
Section: Resultssupporting
confidence: 89%
“…Similar result were previously reported for Drosophila melanogaster [18] and Saccharomyces cerevisiae [19]. The positive association of V E with V G is consistent with the idea that genetic and environmental canalization may have common underlying mechanisms [20], [21], [22]. The positive association between V M and V E has an important implication, because theory predicts that genetic robustness is much more likely to evolve via correlated responses to selection for environmental robustness than via direct selection [11], [20].…”
Section: Resultssupporting
confidence: 89%
“…Previous studies, using gene regulatory network models, have shown that networks will evolve robustness to genetic mutations under conditions of stabilizing selection [13], [14]. This result has been experimentally verified in RNA viruses [15], yeast [16], [17], and in the process of RNA folding [18]. In addition to genetic mutations, organisms are exposed to environmental changes.…”
Section: Introductionmentioning
confidence: 74%
“…A system is robust to genetic or nongenetic perturbations if its phenotype does not change when perturbed. Mutational robustness and robustness to nongenetic perturbations are correlated with one another in many cases (Rutherford & Lindquist, 1998;Ancel & Fontana, 2000;Meiklejohn & Hartl, 2002;de Visser et al, 2003;Ciliberti et al, 2007b;Proulx et al, 2007;Lehner, 2010), although exceptions exist (Cooper et al, 2006;Masel & Siegal, 2009;Fraser & Schadt, 2010). The ability to produce evolutionary innovation is linked to the robustness of a biological system (Ancel & Fontana, 2000;Wagner, 2005;Ciliberti et al, 2007a;Wagner, 2008b;Draghi & Wagner, 2009).…”
Section: Introductionmentioning
confidence: 99%